Analisis Peran Otoritas Jasa Keuangan (Ojk) Dalam Pengawasan Perlindungan Konsumen Terhadap Perkembangan Financial Technology: Peer To Peer Lending - Adinda Alita Septiana; Anggun Sukma Putri; Yeni Winatasari; Endang Kartini Panggiarti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Rapid technological developments have presented various innovations in the financial services sector, namely the presence of Financial Technology. One form of Financial Technology is Peer to Peers Lending, which is an online lending platform that appeared in 2016, was motivated by national economic growth to improve services in the financial sector. Behind the convenience provided by Peer to Peer Lending technology, there is a problem that arises, namely the existence of Financial Technology Peers to Illegal Peer Lending that makes people more interested because of easy access and procedures for making loans online but unnoticed by consumers and the public. Illegal Peer to Peer Lending causes a high risk of default for both parties. The role of the OJK as an independent institution is urgently needed because the legality of the Financial Technology business has high risks related to consumer protection. The research method used by the authors in this article is a qualitative description in which the data source for this research is secondary data with data collection techniques namely literature reviews , analyzing previous research on the topic of the role of the OJK in supervising consumer protection against the development of Financial Technology Peers to Peers lending . From the analysis that has been done, it can be concluded that in dealing with problems that arise as a result of Financial Technology Peers to Peers Illegal lending OJK issued POJK Number 77/POJK.01/2016 concerning information technology-based money lending services and in 2018 OJK issued POJK Number 13/POJK. 02/2018 concerning digital financial innovation in the financial services sector, but unfortunately the regulations issued by the OJK have not been fully able to handle cases of illegal Peer to Peer Lending because the enactment of the POJK does not necessarily make the entities administering the Financial Technology comply. Other steps taken by the OJK in an effort to prevent and supervise acts of fraud by financial technology lending entities are through preventive measures and during operations, as well as conducting selective checks on Peer to Peer Lending companies applying to open new accounts and blocking or closing Peer website applications. To illegal Peer Lending on a regular basis.